2020
DOI: 10.1016/j.medengphy.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Femur strength predictions by nonlinear homogenized voxel finite element models reflect the microarchitecture of the femoral neck

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…10 B and Table 5 ), which was to be expected due to the bone being a highly complex composite material in comparison to PLA. However, the samples tested in this study lie well in the range of reported literature values for human bones which range from an average of 3500 N (for 20 samples tested) [ 51 ] to 6600 N (with a broad scatter range 3780–12,396 N) [ 52 ]. In general, a significant variation in mechanical properties of human bones is observed as values of up to 9196 ± 3177 N [ 40 ] and 8890 ± 377 N [ 43 ] are also reported.…”
Section: Discussionsupporting
confidence: 68%
“…10 B and Table 5 ), which was to be expected due to the bone being a highly complex composite material in comparison to PLA. However, the samples tested in this study lie well in the range of reported literature values for human bones which range from an average of 3500 N (for 20 samples tested) [ 51 ] to 6600 N (with a broad scatter range 3780–12,396 N) [ 52 ]. In general, a significant variation in mechanical properties of human bones is observed as values of up to 9196 ± 3177 N [ 40 ] and 8890 ± 377 N [ 43 ] are also reported.…”
Section: Discussionsupporting
confidence: 68%
“…For each tibia, the cross-section was cut from the midshaft and at 19.5 ± 3.8 cm away from the proximal end of the bone (Iori et al, 2019). For each femur, the cross-section was extracted from the diaphysis at 80 mm below the lesser trochanter (Iori et al, 2020).…”
Section: Specimensmentioning
confidence: 99%
“…Under the stance posture, hip strength has been proposed to be mainly determined by the stiffer cortical compartment, with marginal contributions from trabecular bone 32 . However, over‐adapted femora are particularly fragile under sideways falls, 33 especially in the elderly. A recent experiment has shown that the stance load capacity of the femur is greater than sideways fall load capacity 21 .…”
Section: Discussionmentioning
confidence: 99%